2022
DOI: 10.1073/pnas.2113600119
|View full text |Cite|
|
Sign up to set email alerts
|

Gene evolutionary trajectories in Mycobacterium tuberculosis reveal temporal signs of selection

Abstract: Significance Previous attempts to identify the action of natural selection in the Mycobacterium tuberculosis complex (MTBC) were limited by sample size and averaging across time and lineages. We investigate changes in selective pressures across time for every single gene of the MTBC. We developed a methodology to analyze temporal signals of selection in a large dataset (∼5,000 complete genomes) and showed that 1) almost half of the genes seem to have been under po… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 82 publications
1
20
0
Order By: Relevance
“…The dN/dS of resR was higher in drug-resistant strains compared with drug-sensitive strains (Fig. 1D), suggesting that resR mutations are associated with the evolution of drug resistance and consistent with a recent study showing that resR mutations were associated with a multidrug-resistant tuberculosis (TB) phenotype (8). Protein structural modeling indicated that most resR clinical mutations occur in the merR-type helix-turnhelix DNA-binding domain, with the most common mutations located at the interface between ResR and duplex DNA (Fig.…”
Section: Ongoing Positive Selection In the Mtb Populationsupporting
confidence: 91%
“…The dN/dS of resR was higher in drug-resistant strains compared with drug-sensitive strains (Fig. 1D), suggesting that resR mutations are associated with the evolution of drug resistance and consistent with a recent study showing that resR mutations were associated with a multidrug-resistant tuberculosis (TB) phenotype (8). Protein structural modeling indicated that most resR clinical mutations occur in the merR-type helix-turnhelix DNA-binding domain, with the most common mutations located at the interface between ResR and duplex DNA (Fig.…”
Section: Ongoing Positive Selection In the Mtb Populationsupporting
confidence: 91%
“…The movement or conservation of genes in bacteria is a fundamental factor related to virulence, survival, and host adaptability, allowing them to co-evolve together [ 55 ]. Several studies in M. tuberculosis have shown that the ability of transmission within populations, latency periods, and drug resistance are due to genetic differences within the members of the M. tuberculosis complex and that many of its genes have been under positive selection at different periods [ 56 ]. Furthermore, the composition within its genome remains relatively stable due to the absence of horizontal gene transfer, and this superficial level of genetic variation is probably because these pathogens have a strongly clonal nature [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Filtered reads were mapped with bwa [43] to a predicted MTBC ancestor reference sequence [44] using default parameters, and then processed using the SAMtools [45] and Picard [46] programs. Variant calling was performed with VarScan [47] following published parameters [48]. Once variants had been obtained, we used a mapping filter to discard variants present in repetitive genomic regions such as in PE/PPE gene families or phages [5].…”
Section: Methodsmentioning
confidence: 99%